2021
DOI: 10.1016/j.puhe.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of social responsibility in prevention of the COVID-19 outbreak from systems thinking perspective

Abstract: Due to the lengthy process of producing the COVID-19 vaccine, most countries are trying to implement various low-cost strategies to slow down the spread of the virus and try to normalize the living conditions in society besides reducing the current recession. Comprehension of the cause and effect enables us to analyze, sort out, and explain how changes have happened in the existing problems. In fact, by taking the advantages of Causal Loop Diagrams (CLDs), which reflect the causal connections among components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…The main purpose of this study was to investigate the relationship between sensitivity to anxiety and executive functions and QoL of MS patients and according to the results, there was a relationship between emotional disturbance tolerance and executive functions and QoL in MS patients. Also, these results are in line with the findings of Grech et al indicating the effect of executive function on sensitivity to anxiety and QoL in MS (Figure 1) [9,[24][25][26]. Marck et al and Kos et al showed that there is a relationship between the sensitivity to anxiety and the QoL of people with MS [13,17].…”
Section: Discussionsupporting
confidence: 90%
“…The main purpose of this study was to investigate the relationship between sensitivity to anxiety and executive functions and QoL of MS patients and according to the results, there was a relationship between emotional disturbance tolerance and executive functions and QoL in MS patients. Also, these results are in line with the findings of Grech et al indicating the effect of executive function on sensitivity to anxiety and QoL in MS (Figure 1) [9,[24][25][26]. Marck et al and Kos et al showed that there is a relationship between the sensitivity to anxiety and the QoL of people with MS [13,17].…”
Section: Discussionsupporting
confidence: 90%
“…It is necessary for the governments to take the active role in preventing fake news and infodemic monikers from spreading. Promoting relevant, accurate, and up‐to‐date information on the COVID‐19 pandemic shapes social responsibility, which is essential in fighting COVID‐19 (Hosseini Bamakan & Haddadpoor Jahromi, 2021 ).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…As a result, people may have suffered from loneliness (Nowakowska, 2020 ; Okruszek et al, 2020 ), increased stress (Bodecka et al, 2021 ), anxiety (Gambin et al, 2021 ) and depressive symptoms (Ma et al, 2020 ). The pandemic has been a situation when social responsibility was particularly important, because commitment of the individuals within the society has been required to stop the spread of the virus and mitigate the dramatic costs to health, economy and well-being of entire nations (Hosseini Bamakan & Haddadpoor Jahromi, 2021 ). Previous studies have shown that trust can be a vital factor helping societies to recover from crises (Helliwell et al, 2015 ; Yamamura et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%